Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

An examination of the evidence for and feasibility of a molten silicate basal layer in Mars’ mantle - Stuart Russell; Katrin Hannemann; Sanne Cottaar; Ana-Catalina Plesa; Christine Thomas; Doris Breuer (Icarus, 2026)

An end-to-end model framework for understanding and predicting changes in Antarctic marine ecosystems - Ilari Stollberg; Sophie Bestley; Andrew Constable; Elizabeth A. Fulton; Javier Porobic; David Green; Denise O’Sullivan; Mao Mori; Stuart Corney; Michael Sumner; Jessica Melbourne-Thomas (Ecological Modelling, 2026)

Evaluating a structured expert elicitation approach for adaptive conservation management based on lessons from five years in practice - Helen J. Mayfield; James Brazill‐Boast; Mick Andren; Michiala Bowen; Adam Fawcett; Trent Forge; Luke Foster; Ross Goldingay; Paul Hillier; Meagan Hinds; Simon Lee; Erica Mahon; et al. (Conservation Biology, 2026)
Adaptive management of threatened species relies on having ex ante estimates of species’ responses to different interventions. Structured expert elicitation is often used to generate these estimates, but comparisons of these expert‐predicted outcomes with observed results are rare. This study aims to evaluate the utility of expert elicitation for adaptive management in the New South Wales Saving our Species program in Australia by revisiting six species management plans that were generated from tailored structured elicitation guidelines developed five years prior. Each species’ management plan included a defined scope, conceptual model, monitoring indicators, and estimated response to management curves under different scenarios. Experts reviewed the conceptual models after five years of management and compared the predicted response to management with observed monitoring data. In three of the six case studies, observed outcomes closely matched predictions. Where predictions diverged, factors such as unanticipated new threats and unexpected responses to interventions potentially contributed to discrepancies. However, in all cases, the structured approach provided a clear logic for planning, enabling managers to systematically refine their understanding. The conceptual models and response curves were valuable for collaborating, communicating, and generating hypotheses for unexpected results. This work demonstrates the value of tailored guidelines in supporting adaptive management processes and showcases the value of documenting expert knowledge in management settings with high uncertainty.

Understanding outdoor fitness equipment in South Australia: Insights from council employees and an environmental audit - Alyson J. Crozier; Stuart Gollan; Thomas P. Wycherley; Brad J. Stenner (Journal of Outdoor Recreation and Tourism, 2026)

Cytoplasmic flow dynamics in arbuscular mycorrhizal fungi are intrinsic and independent of plant hosts - Malin Klein; Loreto Oyarte Gálvez; Daniel van der Lugt; Corentin Bisot; Simon van Staalduine; Stuart A. West; Vasilis Kokkoris; Lemeng Dong; Harro Bouwmeester; Thomas S. Shimizu; James T. Weedon; E. Toby Kiers (Fungal Biology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Techno-economic assessment of coal fugitive methane abatement in Australia using currently available technology - Courtney M. Regan; Andy Wilkins; Thomas S. Brinsmead; Richard Mattus; Felicia A. Ruiz; Regina Sander; Nikki Prater; Qingdong Qu; Stuart Addinell (International Journal of Coal Geology, 2026)

Addressing how spatial resolution affects image velocimetry outputs: implications for measurements from space - Harley Dixey; Edward Rollason; Stuart Dunning; Matthew Thomas Perks (Hydrological Sciences Journal, 2026)

RayExtract: A fast, scalable method for tree volume reconstruction from terrestrial laser scanning - Timothy Devereux; Thomas Lowe; Joshua Rivory; Rafael Bohn Reckziegel; Kim Calders; Raja Ram Aryal; Glen Eaton; Zane Cooper; Shaun Levick; Stuart Phinn; William Woodgate (Remote Sensing of Environment, 2026)

Limbic and whole-brain functional connectivity in non-substance abusers with human immunodeficiency virus (HIV) - Stuart D. Washington; Anisa Thomas; Kehinde Omisore; Cedric Cole; Tomilowo Abijo; Ashley VanMeter; Marjorie C. Gondré-Lewis (Journal of NeuroVirology, 2026)

Forest Residue-Derived Thermoresponsive Nanocellulose Adsorbent for Efficient Removal of Short- and Long-Chain PFAS from Water - Md Shahadat Hossain; Thomas Stuart; Aditi Verma; Robert Cheatham; Toufiq Reza; Bandaru Ramarao; Troy Runge; Deepak Kumar (Water, Air, & Soil Pollution, 2026)

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Mapping area of habitat for inland wetland species - Francesca A. Ridley; Catherine A. Sayer; Louise Mair; Daniele Baisero; Monika Böhm; Thomas M. Brooks; Stuart H. M. Butchart; Viola Clausnitzer; Jeorg Freyhof; Günther Grill; Ian Harrison; Randall R. Jiménez; et al. (Conservation Biology, 2026)
Area of habitat (AOH) maps provide a high‐resolution representation of the habitat available in a species’ range and can support conservation policy and planning processes. However, until recently, there was insufficient knowledge on the distribution of inland wetlands and freshwater biodiversity to develop AOH mapping methods specifically tailored to inland wetlands. We used a combined empirical and thematic approach to translate inland wetland habitat classes in the International Union for Conservation of Nature (IUCN) Habitats Classification Scheme into spatially explicit wetland‐cover types derived from the Global Lakes and Wetlands Database 2 and the World Karst Aquifer Map. The AOH was subsequently estimated as the area in the mapped range that corresponded to each species’ habitat and elevation associations. We developed and tested the method with IUCN Red List assessment data, range maps, and point locality data for fishes, odonates, decapod crustaceans, and mollusks (22,876 species). The method performed well in comparison with similar methods already developed for terrestrial mammals, birds, amphibians, and reptiles. The mean map prevalence (proportion of area in a species’ range that was AOH) was 18–32% for each taxonomic group. Based on data on known localities of occurrence, 78–100% of species per taxonomic group had a higher classification accuracy than expected if AOH were distributed in the range at random. This represents an increased accuracy in the distribution of wetland species. Our study represents the first attempt to distinguish between inland wetland habitat subclasses and to include subterranean habitats in an AOH mapping method. Our method will facilitate the inclusion of previously underrepresented taxa in key conservation tools and analyses and is expected to increase the accuracy of AOH mapping for any species associated with inland wetlands.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Enhanced hydrogeochemical baseline of a CO2 injection facility in southern Alberta, Canada - Nicholas Utting; Kirk G. Osadetz; Bernhard Mayer; Tiago Morais; Stuart M.V. Gilfillan; Michael Nightingale; Thomas Darrah; Emma Martin-Roberts; Don Lawton (International Journal of Greenhouse Gas Control, 2026)

He, Ne, and Ar isotope systematics in Chang’e-5 plagioclase reveal diffusive loss and reirradiation processes - Xuhang Zhang; Fei Su; Guillaume Avice; David V. Bekaert; Tomoya Obase; Yuta Otsuki; Finlay M. Stuart; Yingnan Zhang; Jiayan Nie; Xiaoguang Li; Runqing Zhou; Ziheng Liu; et al. (Earth and Planetary Science Letters, 2025)

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Seasonal patterns and multidecadal trends in phytoplankton functional groups in the Benguela upwelling system off Namibia - Tebatso M. Moloto; Marié E. Smith; Thomas G. Bell; Stuart J. Piketh; Sandy J. Thomalla (Science of The Total Environment, 2025)

The effect of source-side subduction on PKP differential times and implications for inner core anisotropy - Stuart Russell; John Keith Magali; Kimberly Vallenton; Christine Thomas (Physics of the Earth and Planetary Interiors, 2025)

Effectiveness of Key Biodiversity Areas in representing global avian diversity - Tom P. Lansley; Olivia Crowe; Stuart H. M. Butchart; David P. Edwards; Gavin H. Thomas (Conservation Biology, 2025)
Key Biodiversity Areas (KBAs) are the largest and most complete network of significant sites for the global persistence of biodiversity. Although important sites for birds worldwide have been relatively well assessed, a key question is how effectively the global KBA network represents avian diversity. We identified bird species, orders, habitats, and geographic regions that are underrepresented by KBAs. Area of Habitat (AOH) maps for 10,517 terrestrial bird species were cropped and masked by the extent of each KBA. Almost all species had at least one part of their seasonal distribution in one or more KBAs. Twenty‐nine species had no habitat overlap with KBAs, and 1900 species had 2 ). Terrestrial bird species of tropical forests were 12.8% better represented in KBAs than expected by chance, whereas boreal and temperate forest species were less well represented than expected by chance (74.4% and 25.1%, respectively). Among avian orders, Anseriformes and Charadriiformes were underrepresented in KBAs (29.0% and 17.9%, respectively), whereas Trogoniformes and Psittaciformes were better represented (16.2% and 6.9%, respectively) than expected by chance. Bird species for potential KBA identification include marsh antwren ( Formicivora paludicola ) and Tabar pitta ( Erythropitta splendida ). These are mainly due to recent changes in species’ taxonomy or their International Union for Conservation of Nature Red List category. Identifying poorly represented species and where they occur highlights shortfalls where expansion of the network could bring conservation benefits.

Vehicles kill birds on sandy beaches: The global evidence - Thomas A. Schlacher; Michael A. Weston; Brooke Maslo; Jenifer E. Dugan; Kyle A. Emery; David M. Hubbard; Brendan P. Kelaher; Mariano Lastra; Stuart E. Parsons (Science of The Total Environment, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Fluid dynamics of dinoflagellate feeding and swimming - Rudi Schuech; Lasse Tor Nielsen; Stuart Humphries; Dave Smith; Thomas Kiørboe (Limnology and Oceanography, 2025)
Flagella are crucial to the interactions of unicellular organisms with their surrounding aquatic environment. One ecologically important group of flagellates, the dinoflagellates, has a unique flagellar arrangement consisting of a trailing and a transversal flagellum. The latter is recessed within a groove around the cell and drives a hair‐bearing membrane that undulates with a helical beat. Dinoflagellates are further unique by having clearance rates that are an order of magnitude higher than those of other similarly sized phagotrophic flagellates, overlapping in size and swimming speed with ciliates. Here, using flow visualization and computational fluid dynamics, we show how this arrangement of just two flagella propels these large cells at high speeds and allows very high clearance rates. We find that the transverse flagellum provides most of the forward thrust, whereas the trailing flagellum is mainly for steering. The flagellar hairs and the sheet‐like structure of the transverse flagellum allow dinoflagellates to exert strong propulsive forces at high efficiency without extending a long flagellum far into the surrounding fluid. The unique flagellar arrangement of dinoflagellates may therefore be key to their evolutionary success.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Adverse impacts of off-road vehicles on coastal dune vegetation are widespread, substantial, and long-lasting: Evidence from a global meta-analysis of sandy beach-dune systems - Thomas A. Schlacher; Michael A. Weston; Shane Orchard; Brendan P. Kelaher; Brooke Maslo; Jenifer E. Dugan; David M. Hubbard; Leonardo Costa; Melanie J. Bishop; Kristal N. Kostoglu; Ben L. Gilby; Christofer J. Henderson; et al. (Estuarine, Coastal and Shelf Science, 2025)

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

Rapid remote volcanic ashfall impact assessment for the 2022 eruption of Hunga volcano, Tonga: a bespoke approach and lessons identified - Alana M. Weir; James H. Williams; Thomas M. Wilson; Josh L. Hayes; Carol Stewart; Graham S. Leonard; Christina Magill; Susanna F. Jenkins; Shaun Williams; Heather M. Craig; Taaniela Kula; Stuart Fraser; et al. (Bulletin of Volcanology, 2024)
When disasters occur, rapid impact assessments are required to prioritise response actions, support in-country efforts and inform the mobilisation of aid. The 15 January 2022 eruption of Hunga volcano, Tonga, and the resulting atmospheric shockwave, ashfall, underwater mass disturbance and tsunami, caused substantial impacts across the Kingdom of Tonga. Volcanic impacts on the scale observed after the eruption are rare, necessitating a reliance on international advice and assistance. The situation was complicated by the loss of Tonga’s international submarine fibreoptic cable (causing a complete loss of communications for approximately 20 days) along with border closures due to the COVID-19 pandemic. A need emerged for a rapid remote volcanic impact assessment and provision of specialist advice to help inform the response of international partners. Here we present a novel methodology for conducting rapid remote volcanic ashfall impact assessments, conducted over a 10-day period following the eruption. We used three different hazard models for ashfall thickness across the main island of Tongatapu and available asset information and vulnerability functions for buildings, agriculture, electricity networks, water supply and roads, to provide initial estimates of losses due to ashfall from the 15 January eruption. For buildings, we estimated losses both as total losses and as percentages of the total replacement cost of buildings on Tongatapu. For agriculture, we made probabilistic estimates of production losses for three different crop classes. For ashfall clean-up, we estimated ranges of ashfall volumes requiring clean-up from road surfaces and roofs. For water supply, electricity networks and roads, our analysis was limited to assessing the exposure of important assets to ashfall, as we had insufficient information on system configurations to take the analysis further. Key constraints on our analysis were the limited nature of critical infrastructure asset inventories and the lack of volcanic vulnerability models for tropical regions including Pacific Island nations. Key steps towards iteratively improving rapid remote impact assessments will include developing vulnerability functions for tropical environments as well as ground-truthing estimated losses from remote approaches against in-person impact assessment campaigns.

Advancing ecosystem services auctions: Insights from an international Delphi panel - Logan Bingham; Peter Boxall; Riccardo Da Re; Stuart Whitten; Thomas Knoke; José G. Borges (Ecosystem Services, 2024)

Accelerating and standardising IUCN Red List assessments with sRedList - Victor Cazalis; Moreno Di Marco; Alexander Zizka; Stuart H.M. Butchart; Manuela González-Suárez; Monika Böhm; Steven P. Bachman; Michael Hoffmann; Ilaria Rosati; Francesco De Leo; Martin Jung; Ana Benítez-López; et al. (Biological Conservation, 2024)

Intracerebral Administration of a Novel Self-Assembling Peptide Hydrogel Is Safe and Supports Cell Proliferation in Experimental Intracerebral Haemorrhage - Faye Bolan; Ben R. Dickie; James R. Cook; Josephine M. Thomas; Emmanuel Pinteaux; Stuart M. Allan; Alberto Saiani; Catherine B. Lawrence (Translational Stroke Research, 2024)
Intracerebral haemorrhage (ICH) is the deadliest form of stroke, but current treatment options are limited, meaning ICH survivors are often left with life-changing disabilities. The significant unmet clinical need and socioeconomic burden of ICH mean novel regenerative medicine approaches are gaining interest. To facilitate the regeneration of the ICH lesion, injectable biomimetic hydrogels are proposed as both scaffolds for endogenous repair and delivery platforms for pro-regenerative therapies. In this paper, the objective was to explore whether injection of a novel self-assembling peptide hydrogel (SAPH) Alpha2 was feasible, safe and could stimulate brain tissue regeneration, in a collagenase-induced ICH model in rats. Alpha2 was administered intracerebrally at 7 days post ICH and functional outcome measures, histological markers of damage and repair and RNA-sequencing were investigated for up to 8 weeks. The hydrogel Alpha2 was safe, well-tolerated and was retained in the lesion for several weeks, where it allowed infiltration of host cells. The hydrogel had a largely neutral effect on functional outcomes and expression of angiogenic and neurogenic markers but led to increased numbers of proliferating cells. RNAseq and pathway analysis showed that ICH altered genes related to inflammatory and phagocytic pathways, and these changes were also observed after administration of hydrogel. Overall, the results show that the novel hydrogel was safe when injected intracerebrally and had no negative effects on functional outcomes but increased cell proliferation. To elicit a regenerative effect, future studies could use a functionalised hydrogel or combine it with an adjunct therapy.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Artificial light and cloud cover interact to disrupt celestial migrations at night - Leo M. Burke; Thomas W. Davies; David Wilcockson; Stuart Jenkins; Amy Ellison (Science of The Total Environment, 2024)

Biogeochemical plumbing of pioneer mangrove intertidal flats in French Guiana - Robert Aller; Issac Klingensmith; Thomas Stieglitz; Christina Heilbrun; Stuart Waugh; Adelaide Aschenbroich; Gerard Thouzeau; Emma Michaud (Regional Environmental Change, 2024)
Migrating mudbanks are characteristic features of the vast Amazon-Guianas coastline along Northeastern South America. As illustrated by sites in French Guiana, consolidating mudflats that periodically transition to mangrove forest are permeated by extensive crustacean burrow systems, sometimes in isolation but more often in close association with morpho-sedimentary structures such as tidal pools and channels. Burrow structures are critical to mangrove growth. In this study, we evaluated the ways in which burrows act as complex conduits that plumb deposits for solute exchange with overlying water. We sampled burrows during low tide when irrigation is inhibited and burrow water rapidly becomes anoxic. The products of diagenetic reactions, for example: NH 4 + , N 2 , and Si(OH) 4 , build up with time, revealing sedimentary reaction rates and fluxes. When oxygenated, burrow walls are zones of intense coupled redox reactions such as nitrification-denitrification. Build-up often is lower in burrows connected directly to tidal pools where photosynthetic activity consumes remineralized nutrients, and burrows can remain periodically irrigated at low tide. During flood, burrows, particularly those that connect tidal pools laterally to channels, can be rapidly flushed and oxygenated as channel water rises and then spreads across flats. Burrow flushing produces enhanced concentrations of nutrients within the leading edge of the flood as seawater moves progressively towards and into adjacent mangroves. Estimates of burrow volumes obtained from drone surveys together with burrow solute production rates allow upscaling of burrow-sourced metabolite fluxes; however, these are extremely variable due to variable burrow geometries, connections between burrows, pools, and channels, and burrow water residence times (oxygenation). The flushing of burrows during flood results in a rectification of sediment-water fluxes shoreward and enhances the delivery of nutrients from the flats into adjacent mangroves and pools, presumably stimulating colonization and forest growth.

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Approaching the challenge of multi-phase, multi-hazard volcanic impact assessment through the lens of systemic risk: application to Taranaki Mounga - Alana M. Weir; Thomas M. Wilson; Mark S. Bebbington; Sarah Beaven; Teresa Gordon; Craig Campbell-Smart; Stuart Mead; James H. Williams; Roger Fairclough (Natural Hazards, 2024)
Effective volcanic impact and risk assessment underpins effective volcanic disaster risk management. Yet contemporary volcanic risk assessments face a number of challenges, including delineating hazard and impact sequences, and identifying and quantifying systemic risks. A more holistic approach to impact assessment is required, which incorporates the complex, multi-hazard nature of volcanic eruptions and the dynamic nature of vulnerability before, during and after a volcanic event. Addressing this need requires a multidisciplinary, integrated approach, involving scientists and stakeholders to co-develop decision-support tools that are scientifically credible and operationally relevant to provide a foundation for robust, evidence-based risk reduction decisions. This study presents a dynamic, longitudinal impact assessment framework for multi-phase, multi-hazard volcanic events and applies the framework to interdependent critical infrastructure networks in the Taranaki region of Aotearoa New Zealand, where Taranaki Mounga volcano has a high likelihood of producing a multi-phase explosive eruption within the next 50 years. In the framework, multi-phase scenarios temporally alternate multi-hazard footprints with risk reduction opportunities. Thus, direct and cascading impacts and any risk management actions carry through to the next phase of activity. The framework forms a testbed for more targeted mitigation and response planning and allows the investigation of optimal intervention timing for mitigation strategies during an evolving eruption. Using ‘risk management’ scenarios, we find the timing of mitigation intervention to be crucial in reducing disaster losses associated with volcanic activity. This is particularly apparent in indirect, systemic losses that cascade from direct damage to infrastructure assets. This novel, dynamic impact assessment approach addresses the increasing end-user need for impact-based decision-support tools that inform robust response and resilience planning.

Presence of non-solar derived krypton and xenon unveiled by Chang'e-5 lunar soils - Xuhang Zhang; Fei Su; Guillaume Avice; Finlay M. Stuart; Yuanyuan Zheng; Ziheng Liu; Wei Guo; Thomas Smith; Runchuan Liu; Chao Lu; Ye He; Jiannan Li; et al. (Earth and Planetary Science Letters, 2024)

Rates of tree cover loss in key biodiversity areas on Indigenous Peoples’ lands - Ashley Thomas Simkins; Paul F. Donald; Alison E. Beresford; Stuart H. M. Butchart; Julia E. Fa; Alvaro Onrubia Fernández‐Llamazares; Stephen T. Garnett; Graeme M. Buchanan (Conservation Biology, 2024)
Indigenous Peoples’ lands (IPL) cover at least 38 million km 2 (28.1%) of Earth's terrestrial surface. These lands can be important for biodiversity conservation. Around 20.7% of IPL intersect areas protected by government (PAs). Many sites of importance for biodiversity within IPL could make a substantial but hitherto unquantified contribution to global site‐based conservation targets. Key Biodiversity Areas (KBAs) represent the largest global network of systematically identified sites of high importance for biodiversity. We assessed the effectiveness of IPL in slowing biodiversity loss inside and outside PAs by quantifying tree cover loss from 2000 to 2019 in KBAs at international and national levels and comparing it with losses at equivalent sites outside mapped IPL. Based on a matched sample of 1‐km 2 cells in KBAs inside and outside mapped IPL, tree cover loss in KBAs outside PAs was lower inside IPL than outside IPL. By contrast, tree cover loss in KBAs inside PAs was lower outside IPL than inside IPL (although the difference was far smaller). National rates of tree cover loss in KBAs varied greatly in relation to their IPL and PA status. In one half of the 44 countries we examined individually, there was no significant difference in the rate of tree cover loss in KBAs inside and outside mapped IPL. The reasons for this intercountry variation could illuminate the importance of IPL in meeting the Convention on Biological Diversity's ambition of conserving 30% of land by 2030. Critical to this will be coordinated action by governments to strengthen and enforce Indigenous Peoples’ rights, secure their collective systems of tenure and governance, and recognize their aspirations for their lands and futures.

Operando synchrotron-based X-ray study and intervention approaches of graphene-related-materials for investigating the performance and durability of HT-PEMFC - Jianuo Chen; Maria Perez-Page; Christopher M.A. Parlett; Zunmin Guo; Xiaochen Yang; Zeyu Zhou; Heng Zhai; Stuart Bartlett; Thomas S. Miller; Stuart M. Holmes (Chemical Engineering Journal, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Interspecies comparison of metabolism of two novel prototype PFAS - Viktória Licul-Kucera; Oddný Ragnarsdóttir; Tobias Frömel; Annemarie P. van Wezel; Thomas P. Knepper; Stuart Harrad; Mohamed Abou-Elwafa Abdallah (Chemosphere, 2024)

Potential for climate change driven spatial mismatches between apple crops and their wild bee pollinators at a continental scale - Leon Marshall; Nicolas Leclercq; Timothy Weekers; Insafe El Abdouni; Luísa G. Carvalheiro; Michael Kuhlmann; Denis Michez; Pierre Rasmont; Stuart P.M. Roberts; Guy Smagghe; Peter Vandamme; Thomas Wood; et al. (Global Environmental Change, 2023)

The importance of time-resolved personal Dosimetry in space: The ISS Crew Active Dosimeter - Ramona Gaza; A. Steve Johnson; Bryan Hayes; Thomas Campbell-Ricketts; Jani Rakkola; Mena Abdelmelek; Cary Zeitlin; Stuart George; Nicholas Stoffle; Andrew Castro; Clif Amberboy; Edward Semones (Life Sciences in Space Research, 2023)

Particle showers detected on ISS in Timepix pixel detectors - Martin Kroupa; Thomas Campbell-Ricketts; Stuart P. George; Amir A. Bahadori; Lawrence S. Pinsky (Life Sciences in Space Research, 2023)

Integrating Menominee model for sustainable forestry with Systems Thinking competency through 3D virtual tours - Ellie Nasr-Azadani; Erica A. H. Smithwick; Stuart J. Steidle; Melissa S. Lucash; Denice H. Wardrop; Nathan T. Fregien; Thomas R. Kenote (Sustainability Science, 2023)
Sustainability competencies enable planners, the public, local communities, academics, and development practitioners to address environmental challenges, better envision the future and devise practical solutions. A key competency in this framework is Systems Thinking, allowing individuals to think comprehensively at different temporal and spatial scales. Among all interested groups, local and Indigenous communities play a significant role in preserving the sustainability of the natural environment and co-producing knowledge based on traditional ecological knowledge. Hence, new approaches are needed to integrate traditional ecological values into competency-based practices to articulate problems and related solutions. This project introduces place-based scenarios rooted in conventional forest management concerning two identified subsets of Bloom’s Taxonomy, Remembering and Understanding, including some competencies necessary for thinking systemically. Overall, 57 participants, including students and staff of the College of Menominee Nation and Menominee community members, in northeast Wisconsin, USA, randomly experienced two visual tools with the same information presented as either: a website with simple 2D images or a 3D virtual tour to investigate which visualization method can help better articulate systems, their components, and behaviors. Participants answered two kinds of questionnaires based on either cognitive mapping or reflection on place-based scenarios. The results show that 3D virtual tour users better demonstrated proficiency in Remembering and Understanding compared to users who experienced the 2D website. Our results thus highlight the potential for 3D virtual experiences to enable sustainability competencies. However, given the observed differences among age and educational groups, future visualization tools and associated research methods should attend to audiences’ competencies, preferences, and comfort, especially among older age groups.

The impact of COVID-19 public health restrictions on particulate matter pollution measured by a validated low-cost sensor network in Oxford, UK - Tony Bush; Suzanne Bartington; Francis D. Pope; Ajit Singh; G. Neil Thomas; Brian Stacey; George Economides; Ruth Anderson; Stuart Cole; Pedro Abreu; Felix C.P. Leach (Building and Environment, 2023)

Wastewater-based monitoring reveals geospatial-temporal trends for antibiotic-resistant pathogens in a large urban community - Zillur Rahman; Weijia Liu; Lara Stapleton; Nikki Kenters; Dewa A.P. Rasmika Dewi; Ori Gudes; Helen Ziochos; Stuart J. Khan; Kaye Power; Mary-Louise McLaws; Torsten Thomas (Environmental Pollution, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

An assessment of the validity and reliability of the P022–P version of e-Celsius core temperature capsules - Thomas W. Service; Katerina Junker; Breanna Service; Cory J. Coehoorn; Marisa Harrington; Steven Martin; Lynneth A. Stuart-Hill (Journal of Thermal Biology, 2023)

Porosity, strength, and alteration – Towards a new volcano stability assessment tool using VNIR-SWIR reflectance spectroscopy - Gabor Kereszturi; Michael Heap; Lauren N. Schaefer; Herlan Darmawan; Frances M. Deegan; Ben Kennedy; Jean-Christophe Komorowski; Stuart Mead; Marina Rosas-Carbajal; Amy Ryan; Valentin R. Troll; Marlène Villeneuve; et al. (Earth and Planetary Science Letters, 2023)

Association between toxic and essential metals in blood and global DNA methylation among electronic waste workers in Agbogbloshie, Ghana - Ibrahim Issah; John Arko-Mensah; Laura S. Rozek; Katie R. Zarins; Duah Dwomoh; Thomas P. Agyekum; Niladri Basu; Stuart Batterman; Thomas G. Robins; Julius N. Fobil (Environmental Science and Pollution Research, 2022)

Topical Collection: Advancements in hydrogeological knowledge of Haiti for recovery and development - James K. Adamson; Alexis Gutierrez; Sergio Perez-Monforte; María Rodriquez-Vera; G. Thomas LaVanchy; Gerald Jean-Baptiste; Evens Emmanuel; Emmanuel Moliere; Richard Gelting; Wm. Javan Miner; Stuart Dykstra (Hydrogeology Journal, 2022)
Haiti’s groundwater resources are poorly understood and scarcely researched, despite their importance as the principal source for water supply. The knowledge gap and its role of inhibiting informed relief, recovery and investments in development are described, along with an update on progress towards the UN Sustainable Development Goals. This essay leads a topical collection of seven articles that advance hydrogeological knowledge of Haiti. Additional data, research and monitoring are identified as urgently needed for the nation’s sustainable development.

Development of Inspired Therapeutics Pediatric VAD: Computational Analysis and Characterization of VAD V3 - Landon H. Tompkins; Barry N. Gellman; Steven R. Prina; Gino F. Morello; Thomas Roussel; Jonathan A. Kopechek; Stuart J. Williams; Priscilla C. Petit; Mark S. Slaughter; Steven C. Koenig; Kurt A. Dasse (Cardiovascular Engineering and Technology, 2022)

Spatial compositional turnover varies with trophic level and body size in marine assemblages of micro‐ and macroorganisms - Amanda K. Pettersen; Melinda A. Coleman; Guillaume Latombe; Sebastian Vadillo Gonzalez; Nathan L. R. Williams; Justin R. Seymour; Alexandra H. Campbell; Torsten Thomas; Renata Ferrari; Rick D. Stuart‐Smith; Graham J. Edgar; Peter D. Steinberg; et al. (Global Ecology and Biogeography, 2022)
Aim Spatial compositional turnover varies considerably among co‐occurring assemblages of organisms, presumably shaped by common processes related to species traits. We investigated patterns of spatial turnover in a diverse set of marine assemblages using zeta diversity, which extends traditional pairwise measures of turnover to capture the roles of both rare and common species in shaping assemblage turnover. We tested the generality of hypothesized patterns related to ecological traits and provide insights into mechanisms of biodiversity change. Location Temperate pelagic and benthic marine assemblages of micro‐ and macroorganisms along south‐eastern Australia (30–36° S latitude). Time period 2008–2021. Major taxa studied Bacteria, phytoplankton, zooplankton, fish, and macrobenthic groups. Methods Six marine datasets spanning bacteria to fishes were collated for measures of “species” occurrence, with a 1° latitude grain. For each assemblage, ecological traits of body size, habitat and trophic level were analysed for the form and rate of decline in zeta diversity and for the species retention rate. Results Species at higher trophic levels showed two to three times the rate of zeta diversity decline compared with lower trophic levels, indicating an increase in turnover from phytoplankton to carnivorous fishes. Body size showed the hypothesized unimodal relationship with rates of turnover for macroorganisms. Patterns of bacterial turnover contrasted with those found for macroorganisms, with the highest levels of turnover in pelagic habitats compared with benthic (kelp‐associated) habitats. The shape of retention rate curves showed the importance of both rare and common species in driving turnover; a finding that would not have been observable using pairwise (beta diversity) measures of turnover. Main conclusions Our results support theoretical predictions for phytoplankton and macroorganisms, showing an increase in turnover rate with trophic level, but these predictions did not hold for bacteria. Such deviations from theory need to be investigated further to identify underlying processes that govern microbial assemblage dynamics.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Development of Inspired Therapeutics Pediatric VAD: Benchtop Evaluation of Impeller Performance and Torques for MagLev Motor Design - Landon H. Tompkins; Steven R. Prina; Barry N. Gellman; Gino F. Morello; Thomas Roussel; Jonathan A. Kopechek; Stuart J. Williams; Priscilla C. Petit; Mark S. Slaughter; Steven C. Koenig; Kurt A. Dasse (Cardiovascular Engineering and Technology, 2022)

Persistent thermally driven shift in the functional trait structure of herbivorous fishes: Evidence of top‐down control on the rebound potential of temperate seaweed forests? - Nestor E. Bosch; Matthew McLean; Salvador Zarco‐Perello; Scott Bennett; Rick D. Stuart‐Smith; Adriana Vergés; Albert Pessarrodona; Fernando Tuya; Tim Langlois; Claude Spencer; Sahira Bell; Benjamin J. Saunders; et al. (Global Change Biology, 2022)
Extreme climatic events can reshape the functional structure of ecological communities, potentially altering ecological interactions and ecosystem functioning. While these shifts have been widely documented, evidence of their persistence and potential flow‐on effects on ecosystem structure following relaxation of extreme events remains limited. Here, we investigate changes in the functional trait structure – encompassing dimensions of resource use, thermal affinity, and body size – of herbivorous fishes in a temperate reef system that experienced an extreme marine heatwave (MHW) and subsequent return to cool conditions. We quantify how changes in the trait structure modified the nature and intensity of herbivory‐related functions (macroalgae, turf, and sediment removal), and explored the potential flow‐on effects on the recovery dynamics of macroalgal foundation species. The trait structure of the herbivorous fish assemblage shifted as a result of the MHW, from dominance of cool‐water browsing species to increased evenness in the distribution of abundance among temperate and tropical guilds supporting novel herbivory roles (i.e. scraping, cropping, and sediment sucking). Despite the abundance of tropical herbivorous fishes and intensity of herbivory‐related functions declined following a period of cooling after the MHW, the underlying trait structure displayed limited recovery. Concomitantly, algal assemblages displayed a lack of recovery of the formerly dominant foundational species, the kelp Ecklonia radiata , transitioning to an alternative state dominated by turf and Sargassum spp. Our study demonstrates a legacy effect of an extreme MHW and exemplified the value of monitoring phenotypic (trait mediated) changes in the nature of core ecosystem processes to predict and adapt to the future configurations of changing reef ecosystems.

Warming world, changing ocean: mitigation and adaptation to support resilient marine systems - Rowan Trebilco; Aysha Fleming; Alistair J. Hobday; Jess Melbourne-Thomas; Amelie Meyer; Jan McDonald; Phillipa C. McCormack; Kelli Anderson; Narissa Bax; Stuart P. Corney; Leo X. C. Dutra; Hannah E. Fogarty; et al. (Reviews in Fish Biology and Fisheries, 2022)

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Increasing the spatial and temporal impact of ecological research: A roadmap for integrating a novel terrestrial process into an Earth system model - Emily Kyker‐Snowman; Danica L. Lombardozzi; Gordon B. Bonan; Susan J. Cheng; Jeffrey S. Dukes; Serita D. Frey; Elin M. Jacobs; Risa McNellis; Joshua M. Rady; Nicholas G. Smith; R. Quinn Thomas; William R. Wieder; et al. (Global Change Biology, 2022)
Terrestrial ecosystems regulate Earth's climate through water, energy, and biogeochemical transformations. Despite a key role in regulating the Earth system, terrestrial ecology has historically been underrepresented in the Earth system models (ESMs) that are used to understand and project global environmental change. Ecology and Earth system modeling must be integrated for scientists to fully comprehend the role of ecological systems in driving and responding to global change. Ecological insights can improve ESM realism and reduce process uncertainty, while ESMs offer ecologists an opportunity to broadly test ecological theory and increase the impact of their work by scaling concepts through time and space. Despite this mutualism, meaningfully integrating the two remains a persistent challenge, in part because of logistical obstacles in translating processes into mathematical formulas and identifying ways to integrate new theories and code into large, complex model structures. To help overcome this interdisciplinary challenge, we present a framework consisting of a series of interconnected stages for integrating a new ecological process or insight into an ESM. First, we highlight the multiple ways that ecological observations and modeling iteratively strengthen one another, dispelling the illusion that the ecologist's role ends with initial provision of data. Second, we show that many valuable insights, products, and theoretical developments are produced through sustained interdisciplinary collaborations between empiricists and modelers, regardless of eventual inclusion of a process in an ESM. Finally, we provide concrete actions and resources to facilitate learning and collaboration at every stage of data‐model integration. This framework will create synergies that will transform our understanding of ecology within the Earth system, ultimately improving our understanding of global environmental change, and broadening the impact of ecological research.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Global DNA (LINE-1) methylation is associated with lead exposure and certain job tasks performed by electronic waste workers - Ibrahim Issah; John Arko-Mensah; Laura S. Rozek; Katie R. Zarins; Thomas P. Agyekum; Duah Dwomoh; Niladri Basu; Stuart Batterman; Thomas G. Robins; Julius N. Fobil (International Archives of Occupational and Environmental Health, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Geological and hydrogeological assessment of the Brito Formation: Municipio de Tola, Nicaragua - James K. Adamson; G. Thomas LaVanchy; Brandon Stone; James A. Clark; Stuart J. Dykstra; Matthew J. Taylor (Hydrogeology Journal, 2021)
There are sparse hydrogeological data and insufficient hydrogeological knowledge in many areas of the world reliant on groundwater. Nicaragua’s Pacific coast is one such region that is also experiencing water scarcity resulting from increasing demand on groundwater resources and climate change. The primary source of water in the region is the aquifer system associated with the Brito Formation, which is a marine sedimentary stratum of mostly sandstone that blankets 75 km of coastline in southwest Nicaragua. This study focused on the Tola municipality with the objective to advance a conceptual understanding of the hydrogeology and to support sustainable water development. Results demonstrate a heterogeneous aquifer system with regional flow characteristics and other factors that influence groundwater availability and water quality. Primary porosity is low, and secondary porosity is the primary mechanism of aquifer storage and is influenced by geological structure and diagenesis processes. Groundwater recharge is spatially and temporally heterogeneous and direct recharge is low. Infiltration of streamflow and runoff, especially early in the rainy season, is thought to be a large component of groundwater recharge. Climate, flow and recharge dynamics, and low storage capacity make the Brito Formation a sensitive resource and vulnerable to drought, increased abstraction, and climate change. This assessment provides data and insights useful for informing future studies and investments within the region and may be applicable in other Central American and Caribbean nations with coastal sandstone aquifers.

Characterization of basal forebrain glutamate neurons suggests a role in control of arousal and avoidance behavior - James T. McKenna; Chun Yang; Thomas Bellio; Marissa B. Anderson-Chernishof; Mackenzie C. Gamble; Abigail Hulverson; John G. McCoy; Stuart Winston; Erik Hodges; Fumi Katsuki; James M. McNally; Radhika Basheer; et al. (Brain Structure and Function, 2021)

Diffusion MRI as a complementary assessment to cognition, emotion, and motor dysfunction after sports-related concussion: a systematic review and critical appraisal of the literature - Sarah C. Hellewell; Thomas Welton; Alan J. Pearce; Jerome J. Maller; Stuart M. Grieve (Brain Imaging and Behavior, 2021)

Correction to: TCA cycle metabolic compromise due to an aberrant S‑nitrosoproteome in HIV‑associated neurocognitive disorder with methamphetamine use - Paschalis‑Thomas Doulias; Tomohiro Nakamura; Henry Scott; Scott R. McKercher; Abdullah Sultan; Amanda Deal; Matthew Albertolle; Harry Ischiropoulos; Stuart A. Lipton (Journal of NeuroVirology, 2021)

TCA cycle metabolic compromise due to an aberrant S-nitrosoproteome in HIV-associated neurocognitive disorder with methamphetamine use - Paschalis-Thomas Doulias; Tomohiro Nakamura; Henry Scott; Scott R. McKercher; Abdullah Sultan; Amanda Deal; Matthew Albertolle; Harry Ischiropoulos; Stuart A. Lipton (Journal of NeuroVirology, 2021)

The functions and regulation of heat shock proteins; key orchestrators of proteostasis and the heat shock response - Benjamin J. Lang; Martin E. Guerrero; Thomas L. Prince; Yuka Okusha; Cristina Bonorino; Stuart K. Calderwood (Archives of Toxicology, 2021)

Sexual Mismatch Between Vessel-Associated Foraging and Discard Consumption in a Marine Top Predator - Joan Giménez; Gavin E. Arneill; Ashley Bennison; Enrico Pirotta; Hans D. Gerritsen; Thomas W. Bodey; Stuart Bearhop; Keith C. Hamer; Stephen Votier; Mark Jessopp (Frontiers in Marine Science, 2021)
Sex differences in diet and foraging behaviour are common in sexually dimorphic species, often driven by differences in the cost of locomotion or ability to exploit different ecological niches. However, sex-specific foraging strategies also occur in monomorphic or slightly dimorphic species where the drivers are poorly understood. Here, we study sex differences in foraging of northern gannets ( Morus bassanus ), where females are only slightly heavier than males. Using concurrently tracked gannets (298 full foraging trips from 81 individuals) and fishing vessels across 5 years, we quantify individual-based vessel-associated putative foraging, and relate this to discard consumption. We found a significant positive relationship between time spent in vessel-associated foraging and discard consumption for both sexes. However, while females showed greater proportions of vessel-associated foraging than males, discarded fish contributed less to the diet of females in all years. These results contrast with previous suggestions that female gannets interact with vessels less often than males, and are consistent with competitive exclusion of females from trawler-associated discards. Our findings give insight into sexual differences in foraging behaviour in the absence of dimorphism that are necessary to predict their response to environmental and anthropogenic changes.

Ecotrons: Powerful and versatile ecosystem analysers for ecology, agronomy and environmental science - Jacques Roy; François Rineau; Hans J. De Boeck; Ivan Nijs; Thomas Pütz; Samuel Abiven; John A. Arnone; Craig V. M. Barton; Natalie Beenaerts; Nicolas Brüggemann; Matteo Dainese; Timo Domisch; et al. (Global Change Biology, 2021)
Ecosystems integrity and services are threatened by anthropogenic global changes. Mitigating and adapting to these changes require knowledge of ecosystem functioning in the expected novel environments, informed in large part through experimentation and modelling. This paper describes 13 advanced controlled environment facilities for experimental ecosystem studies, herein termed ecotrons, open to the international community. Ecotrons enable simulation of a wide range of natural environmental conditions in replicated and independent experimental units while measuring various ecosystem processes. This capacity to realistically control ecosystem environments is used to emulate a variety of climatic scenarios and soil conditions, in natural sunlight or through broad‐spectrum lighting. The use of large ecosystem samples, intact or reconstructed, minimizes border effects and increases biological and physical complexity. Measurements of concentrations of greenhouse trace gases as well as their net exchange between the ecosystem and the atmosphere are performed in most ecotrons, often quasi continuously. The flow of matter is often tracked with the use of stable isotope tracers of carbon and other elements. Equipment is available for measurements of soil water status as well as root and canopy growth. The experiments ran so far emphasize the diversity of the hosted research. Half of them concern global changes, often with a manipulation of more than one driver. About a quarter deal with the impact of biodiversity loss on ecosystem functioning and one quarter with ecosystem or plant physiology. We discuss how the methodology for environmental simulation and process measurements, especially in soil, can be improved and stress the need to establish stronger links with modelling in future projects. These developments will enable further improvements in mechanistic understanding and predictive capacity of ecotron research which will play, in complementarity with field experimentation and monitoring, a crucial role in exploring the ecosystem consequences of environmental changes.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Nitrate respiration and diel migration patterns of diatoms are linked in sediments underneath a microbial mat - Elisa Merz; Gregory J. Dick; Dirk de Beer; Sharon Grim; Thomas Hübener; Sten Littmann; Kirk Olsen; Dack Stuart; Gaute Lavik; Hannah K. Marchant; Judith M. Klatt (Environmental Microbiology, 2021)
Summary Diatoms are among the few eukaryotes known to store nitrate (NO 3 − ) and to use it as an electron acceptor for respiration in the absence of light and O 2 . Using microscopy and 15 N stable isotope incubations, we studied the relationship between dissimilatory nitrate/nitrite reduction to ammonium (DNRA) and diel vertical migration of diatoms in phototrophic microbial mats and the underlying sediment of a sinkhole in Lake Huron (USA). We found that the diatoms rapidly accumulated NO 3 − at the mat‐water interface in the afternoon and 40% of the population migrated deep into the sediment, where they were exposed to dark and anoxic conditions for ~75% of the day. The vertical distribution of DNRA rates and diatom abundance maxima coincided, suggesting that DNRA was the main energy generating metabolism of the diatom population. We conclude that the illuminated redox‐dynamic ecosystem selects for migratory diatoms that can store nitrate for respiration in the absence of light. A major implication of this study is that the dominance of DNRA over denitrification is not explained by kinetics or thermodynamics. Rather, the dynamic conditions select for migratory diatoms that perform DNRA and can outcompete sessile denitrifiers.

Scavenging amphipods from the Wallaby-Zenith Fracture Zone: Extending the hadal paradigm beyond subduction trenches - Johanna N. J. Weston; Rachael A. Peart; Heather A. Stewart; Heather Ritchie; Stuart B. Piertney; Thomas D. Linley; Alan J. Jamieson (Marine Biology, 2021)
Our understanding of the ecology of the hadal zone (> 6000 m depth) is based solely on subduction trenches, leaving other geomorphological features, such as fracture zones, troughs, and basins, understudied. To address this knowledge gap, the Wallaby-Zenith Fracture Zone, Indian Ocean (WZFZ; ~ 22°S, 102°E; maximum depth 6625 m measured during Expedition SO258) was studied using free-fall baited landers. We assessed the amphipod distribution and community assemblage of this non-subduction hadal feature and compared it to subduction hadal features. Eleven species were identified across the abyssal-hadal transition zone using a paired morphological and DNA barcoding approach. The community composition was found to change gradually from abyssal to hadal depths, which contrasts with the ecotone shift characteristic of subduction trenches. A large population of Bathycallisoma schellenbergi (Birstein & Vinogradov, 1958), a quintessential hadal amphipod, was present at the flat bottom of the WZFZ. Further, an mtDNA phylogeny resolved a degree of phylogeographic structure between the B. schellenbergi WZFZ population and four previously sampled Pacific Ocean subduction trench populations, indicating these features are not interconnected through ongoing gene flow. Combined, these data indicate that some amphipods have far broader distributions than previously understood, with some species present in both hadal subduction trenches and non-subduction fracture zones and basins interspersed across the abyssal plains. This initial exploration highlights that whilst non-subduction features are an overlooked minor fraction of the total hadal area, they are essential to our understanding of the ecological and evolutionary dynamics across the hadal zone.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Influence of the subtropical ridge on directional wave power in the southeast Indian Ocean - Thomas R. Mortlock; Zak Baillie; Ian D. Goodwin; Stuart Browning (International Journal of Climatology, 2020)
Changes in the intensity and position of subtropical anticyclones are major drivers of wave climate around Australia. The quasi‐stationary ridge of high atmospheric pressure in the mid‐latitudes is known as the Subtropical Ridge (STR). In this study, we decompose the directional wave climate along the Western Australian Shelf (WAS) into three primary modes of variability using a statistical‐synoptic typing approach, and relate the wave power signatures of each to movements in the STR. We find a significant reduction in wave power along the WAS over the past 35 years. This is synonymous with an intensification of the STR resulting in blocking of powerful Southern Ocean Low wave conditions, a small increase in weaker anticyclonic waves, and a reduction in total wave power. A persistent intensification and/or poleward shift in the STR, associated with anthropogenic warming, may result in a continued decrease and anticlockwise rotation in wave power along the WAS. The approach taken in this article relates empirical changes in wave climate to movements in large‐scale climate drivers which can be used to complement the understanding of climate‐model based scenarios of wave climate change.

Time-Dynamic Food Web Modeling to Explore Environmental Drivers of Ecosystem Change on the Kerguelen Plateau - Roshni C. Subramaniam; Jessica Melbourne-Thomas; Stuart P. Corney; Karen Alexander; Clara Péron; Philippe Ziegler; Kerrie M. Swadling (Frontiers in Marine Science, 2020)

Association mapping of malting quality traits in UK spring and winter barley cultivar collections - Mark E. Looseley; Luke Ramsay; Hazel Bull; J. Stuart Swanston; Paul D. Shaw; Malcolm Macaulay; Allan Booth; Joanne R. Russell; Robbie Waugh; William T. B. Thomas (Theoretical and Applied Genetics, 2020)
Key message Historical malting quality data was collated from UK national and recommended list trial data and used in a GWAS. 25 QTL were identified, with the majority from spring barley cultivar sets. Abstract In Europe, the most economically significant use of barley is the production of malt for use in the brewing and distilling industries. As such, selection for traits related to malting quality is of great commercial interest. In order to study the genetic basis of variation for malting quality traits in UK cultivars, a historical set of trial data was collated from national and recommended list trials from the period 1988 to 2016. This data was used to estimate variety means for 20 quality related traits in 451 spring barley cultivars, and 407 winter cultivars. Genotypes for these cultivars were generated using iSelect 9k and 50k genotyping platforms, and a genome wide association scan performed to identify malting quality quantitative trait loci (QTL). 24 QTL were identified in spring barley cultivars, and 2 from the winter set. A number of these correspond to known malting quality related genes but the remainder represents novel genetic variation that is accessible to breeders for the genetic improvement of new cultivars.

Capacity challenges in water quality monitoring: understanding the role of human development - Sabrina Kirschke; Tamara Avellán; Ilona Bärlund; Janos J. Bogardi; Laurence Carvalho; Deborah Chapman; Chris W. S. Dickens; Kenneth Irvine; SungBong Lee; Thomas Mehner; Stuart Warner (Environmental Monitoring and Assessment, 2020)
Monitoring the qualitative status of freshwaters is an important goal of the international community, as stated in the Sustainable Development Goal (SDGs) indicator 6.3.2 on good ambient water quality. Monitoring data are, however, lacking in many countries, allegedly because of capacity challenges of less-developed countries. So far, however, the relationship between human development and capacity challenges for water quality monitoring have not been analysed systematically. This hinders the implementation of fine-tuned capacity development programmes for water quality monitoring. Against this background, this study takes a global perspective in analysing the link between human development and the capacity challenges countries face in their national water quality monitoring programmes. The analysis is based on the latest data on the human development index and an international online survey amongst experts from science and practice. Results provide evidence of a negative relationship between human development and the capacity challenges to meet SDG 6.3.2 monitoring requirements. This negative relationship increases along the course of the monitoring process, from defining the enabling environment, choosing parameters for the collection of field data, to the analytics and analysis of five commonly used parameters (DO, EC, pH, TP and TN). Our assessment can be used to help practitioners improve technical capacity development activities and to identify and target investment in capacity development for monitoring.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Using time-series similarity measures to compare animal movement trajectories in ecology - Ian R. Cleasby; Ewan D. Wakefield; Barbara J. Morrissey; Thomas W. Bodey; Steven C. Votier; Stuart Bearhop; Keith C. Hamer (Behavioral Ecology and Sociobiology, 2019)
Identifying and understanding patterns in movement data are amongst the principal aims of movement ecology. By quantifying the similarity of movement trajectories, inferences can be made about diverse processes, ranging from individual specialisation to the ontogeny of foraging strategies. Movement analysis is not unique to ecology however, and methods for estimating the similarity of movement trajectories have been developed in other fields but are currently under-utilised by ecologists. Here, we introduce five commonly used measures of trajectory similarity: dynamic time warping (DTW), longest common subsequence (LCSS), edit distance for real sequences (EDR), Fréchet distance and nearest neighbour distance (NND), of which only NND is routinely used by ecologists. We investigate the performance of each of these measures by simulating movement trajectories using an Ornstein-Uhlenbeck (OU) model in which we varied the following parameters: (1) the point of attraction, (2) the strength of attraction to this point and (3) the noise or volatility added to the movement process in order to determine which measures were most responsive to such changes. In addition, we demonstrate how these measures can be applied using movement trajectories of breeding northern gannets ( Morus bassanus ) by performing trajectory clustering on a large ecological dataset. Simulations showed that DTW and Fréchet distance were most responsive to changes in movement parameters and were able to distinguish between all the different parameter combinations we trialled. In contrast, NND was the least sensitive measure trialled. When applied to our gannet dataset, the five similarity measures were highly correlated despite differences in their underlying calculation. Clustering of trajectories within and across individuals allowed us to easily visualise and compare patterns of space use over time across a large dataset. Trajectory clusters reflected the bearing on which birds departed the colony and highlighted the use of well-known bathymetric features. As both the volume of movement data and the need to quantify similarity amongst animal trajectories grow, the measures described here and the bridge they provide to other fields of research will become increasingly useful in ecology. Significance statement As the use of tracking technology increases, there is a need to develop analytical techniques to process such large volumes of data. One area in which this would be useful is the comparison of individual movement trajectories. In response, a variety of measures of trajectory similarity have been developed within the information sciences. However, such measures are rarely used by ecologists who may be unaware of them. To remedy this, we apply five common measures of trajectory similarity to both simulated data and real ecological dataset comprising of movement trajectories of breeding northern gannets. Dynamic time warping and Fréchet distance performed best on simulated data. Using trajectory similarity measures on our gannet dataset, we identified distinct foraging clusters centred on different bathymetric features, demonstrating one application of such similarity measures. As new technology and analysis techniques proliferate across ecology and the information sciences, closer ties between these fields promise further innovative analysis of movement data.

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Four priorities for new links between conservation science and accounting research - Clément Feger; Laurent Mermet; Bhaskar Vira; Prue F.E. Addison; Richard Barker; Frank Birkin; John Burns; Stuart Cooper; Denis Couvet; Thomas Cuckston; Gretchen C. Daily; Colin Dey; et al. (Conservation Biology, 2019)
Article impact statement : New collaborations with accounting research can improve conservation impact of ecosystem‐based information systems.

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Incorporating social dimensions in planning, managing and evaluating environmental projects - C. Louise Goggin; Thomas Barrett; John Leys; Gregory Summerell; Emma Gorrod; Stuart Waters; Mark Littleboy; Tony D. Auld; Michael J. Drielsma; Brian R. Jenkins (Environmental Management, 2019)

Effects of hybridization on sea turtle fitness - Luciano S. Soares; Karen A. Bjorndal; Alan B. Bolten; Maria A. G. dei Marcovaldi; Pedro B. Luz; Rodrigo Machado; Rachel Lo; Stuart F. McDaniel; Adam C. Payton; Thomas B. Waltzek; Marta L. Wayne (Conservation Genetics, 2018)

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Determining the potential sites of neural adaptation to cross-education: implications for the cross-education of muscle strength - Ashlyn K. Frazer; Alan J. Pearce; Glyn Howatson; Kevin Thomas; Stuart Goodall; Dawson J. Kidgell (European Journal of Applied Physiology, 2018)

Rapid ecosystem service assessment of the impact of Koshi Tappu Wildlife Reserve on wetland benefits to local communities - Jennifer C. Merriman; Hum Gurung; Shalu Adhikari; Stuart H. M. Butchart; Top B. Khatri; Ravi S. Pandit; Ashok K. Ram; David H. L. Thomas; Ishana Thapa (Wetlands Ecology and Management, 2018)

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Progress in designing and delivering effective fishing industry–science data collection in the UK - Stephen C Mangi; Sven Kupschus; Steven Mackinson; Dale Rodmell; Alexandra Lee; Elizabeth Bourke; Tom Rossiter; Jim Masters; Stuart Hetherington; Thomas Catchpole; David Righton (Fish and Fisheries, 2018)
This study was undertaken to address the increasing need for a strategic approach to industry–science data collections in the face of reducing resources and growing need for evidence in fisheries management. The aim was to evaluate progress in the development of plans and procedures that can be employed to collect, record and use fishing industry knowledge and data in the evidence base for managing fisheries. This was achieved by reviewing industry‐led data initiatives already undertaken or ongoing within the United Kingdom to document how these projects have/are incorporating fishing industry data into the process of management decision‐making; canvassing stakeholder opinion on data gaps and whether these could be filled by data gathered by commercial fishing vessels; establishing what issues might prevent or stimulate commercial fishing vessels in collecting data when they have the opportunity; and describing guidance on a step‐by‐step process for gathering scientific information such that fishers are empowered to collect the right data, at the right times and in the right format for their fishery. Given recent advances in the collection, interpretation and application of fisheries‐dependent data, we compare progress made in the UK to other areas of the world. We conclude that there is considerable evidence of a paradigm shift from the conventional practice of scientists asking fishers to provide data for scientific analyses towards full engagement of key stakeholders in data collection.

Clarifying the key biodiversity areas partnership and programme - Simon N. Stuart; Thomas M. Brooks; Stuart H. M. Butchart; Wendy Elliott; Melanie Heath; Dieter Hoffmann; Leslie Honey; Irina Kostadinova; Penny Langhammer; Olivier Langrand; Susan Lieberman; Daniel Marnewick; et al. (Biodiversity and Conservation, 2018)

Modulation of specific inhibitory networks in fatigued locomotor muscles of healthy males - Stuart Goodall; Glyn Howatson; Kevin Thomas (Experimental Brain Research, 2018)

A Synergistic Approach for Evaluating Climate Model Output for Ecological Applications - Rachel D. Cavanagh; Eugene J. Murphy; Thomas J. Bracegirdle; John Turner; Cheryl A. Knowland; Stuart P. Corney; Walker O. Smith; Claire M. Waluda; Nadine M. Johnston; Richard G. J. Bellerby; Andrew J. Constable; Daniel P. Costa; et al. (Frontiers in Marine Science, 2017)

The assessment of neuromuscular fatigue during 120 min of simulated soccer exercise - Stuart Goodall; Kevin Thomas; Liam David Harper; Robert Hunter; Paul Parker; Emma Stevenson; Daniel West; Mark Russell; Glyn Howatson (European Journal of Applied Physiology, 2017)

Mechanisms driving Antarctic microbial community responses to ocean acidification: a network modelling approach - Roshni C. Subramaniam; Jessica Melbourne-Thomas; Andrew T. Davidson; Stuart P. Corney (Polar Biology, 2017)

Body size drives allochthony in food webs of tropical rivers - Timothy D. Jardine; Thomas S. Rayner; Neil E. Pettit; Dominic Valdez; Douglas P. Ward; Garry Lindner; Michael M. Douglas; Stuart E. Bunn (Oecologia, 2017)

Determinants of bird conservation‐action implementation and associated population trends of threatened species - David A. Luther; Thomas M. Brooks; Stuart H.M. Butchart; Matt W. Hayward; Marieke E. Kester; John Lamoreux; Amy Upgren (Conservation Biology, 2016)
Conservation actions, such as habitat protection, attempt to halt the loss of threatened species and help their populations recover. The efficiency and the effectiveness of actions have been examined individually. However, conservation actions generally occur simultaneously, so the full suite of implemented conservation actions should be assessed. We used the conservation actions underway for all threatened and near‐threatened birds of the world (International Union for Conservation of Nature Red List of Threatened Species) to assess which biological (related to taxonomy and ecology) and anthropogenic (related to geoeconomics) factors were associated with the implementation of different classes of conservation actions. We also assessed which conservation actions were associated with population increases in the species targeted. Extinction‐risk category was the strongest single predictor of the type of conservation actions implemented, followed by landmass type (continent, oceanic island, etc.) and generation length. Species targeted by invasive nonnative species control or eradication programs, ex situ conservation, international legislation, reintroduction, or education, and awareness‐raising activities were more likely to have increasing populations. These results illustrate the importance of developing a predictive science of conservation actions and the relative benefits of each class of implemented conservation action for threatened and near‐threatened birds worldwide.

Quantifying the relative irreplaceability of important bird and biodiversity areas - Moreno Di Marco; Thomas Brooks; Annabelle Cuttelod; Lincoln D.C. Fishpool; Carlo Rondinini; Robert J. Smith; Leon Bennun; Stuart H.M. Butchart; Simon Ferrier; Ruud P.B. Foppen; Lucas Joppa; Diego Juffe‐Bignoli; et al. (Conservation Biology, 2016)
World governments have committed to increase the global protected areas coverage by 2020, but the effectiveness of this commitment for protecting biodiversity depends on where new protected areas are located. Threshold‐ and complementarity‐based approaches have been independently used to identify important sites for biodiversity. We brought together these approaches by performing a complementarity‐based analysis of irreplaceability in important bird and biodiversity areas (IBAs), which are sites identified using a threshold‐based approach. We determined whether irreplaceability values are higher inside than outside IBAs and whether any observed difference depends on known characteristics of the IBAs. We focused on 3 regions with comprehensive IBA inventories and bird distribution atlases: Australia, southern Africa, and Europe. Irreplaceability values were significantly higher inside than outside IBAs, although differences were much smaller in Europe than elsewhere. Higher irreplaceability values in IBAs were associated with the presence and number of restricted‐range species; number of criteria under which the site was identified; and mean geographic range size of the species for which the site was identified (trigger species). In addition, IBAs were characterized by higher irreplaceability values when using proportional species representation targets, rather than fixed targets. There were broadly comparable results when measuring irreplaceability for trigger species and when considering all bird species, which indicates a good surrogacy effect of the former. Recently, the International Union for Conservation of Nature has convened a consultation to consolidate global standards for the identification of key biodiversity areas (KBAs), building from existing approaches such as IBAs. Our results informed this consultation, and in particular a proposed irreplaceability criterion that will allow the new KBA standard to draw on the strengths of both threshold‐ and complementarity‐based approaches.

Genotypic variation in foundation species generates network structure that may drive community dynamics and evolution - Matthew K. Lau; Arthur R. Keith; Stuart R. Borrett; Stephen M. Shuster; Thomas G. Whitham (Ecology, 2016)
Although genetics in a single species is known to impact whole communities, little is known about how genetic variation influences species interaction networks in complex ecosystems. Here, we examine the interactions in a community of arthropod species on replicated genotypes (clones) of a foundation tree species, Populus angustifolia James (narrowleaf cottonwood), in a long‐term, common garden experiment using a bipartite “genotype–species” network perspective. We combine this empirical work with a simulation experiment designed to further investigate how variation among individual tree genotypes can impact network structure. Three findings emerged: (1) the empirical “genotype–species network” exhibited significant network structure with modularity being greater than the highly conservative null model; (2) as would be expected given a modular network structure, the empirical network displayed significant positive arthropod co‐occurrence patterns; and (3) furthermore, the simulations of “genotype–species” networks displayed variation in network structure, with modularity in particular clearly increasing, as genotypic variation increased. These results support the conclusion that genetic variation in a single species contributes to the structure of ecological interaction networks, which could influence ecological dynamics (e.g., assembly and stability) and evolution in a community context.

Life cycle assessment of lignocellulosic biomass pretreatment methods in biofuel production - Aashish Prasad; Maria Sotenko; Thomas Blenkinsopp; Stuart R. Coles (The International Journal of Life Cycle Assessment, 2016)

Bridging the gap between omics and earth system science to better understand how environmental change impacts marine microbes - Thomas Mock; Stuart J. Daines; Richard Geider; Sinead Collins; Metodi Metodiev; Andrew J. Millar; Vincent Moulton; Timothy M. Lenton (Global Change Biology, 2016)
The advent of genomic‐, transcriptomic‐ and proteomic‐based approaches has revolutionized our ability to describe marine microbial communities, including biogeography, metabolic potential and diversity, mechanisms of adaptation, and phylogeny and evolutionary history. New interdisciplinary approaches are needed to move from this descriptive level to improved quantitative, process‐level understanding of the roles of marine microbes in biogeochemical cycles and of the impact of environmental change on the marine microbial ecosystem. Linking studies at levels from the genome to the organism, to ecological strategies and organism and ecosystem response, requires new modelling approaches. Key to this will be a fundamental shift in modelling scale that represents micro‐organisms from the level of their macromolecular components. This will enable contact with omics data sets and allow acclimation and adaptive response at the phenotype level (i.e. traits) to be simulated as a combination of fitness maximization and evolutionary constraints. This way forward will build on ecological approaches that identify key organism traits and systems biology approaches that integrate traditional physiological measurements with new insights from omics. It will rely on developing an improved understanding of ecophysiology to understand quantitatively environmental controls on microbial growth strategies. It will also incorporate results from experimental evolution studies in the representation of adaptation. The resulting ecosystem‐level models can then evaluate our level of understanding of controls on ecosystem structure and function, highlight major gaps in understanding and help prioritize areas for future research programs. Ultimately, this grand synthesis should improve predictive capability of the ecosystem response to multiple environmental drivers.

Structural Characterisation of Non-Deamidated Acidic Variants of Erwinia chrysanthemi L-asparaginase Using Small-Angle X-ray Scattering and Ion-Mobility Mass Spectrometry - David Gervais; Darryl King; Patrick Kanda; Nicholas Foote; Lucy Elliott; Phillip Brown; Natacha O. Lee; Konstantinos Thalassinos; Claire Pizzey; Robert Rambo; Thomas C. Minshull; Mark J. Dickman; et al. (Pharmaceutical Research, 2015)

Long‐term individual foraging site fidelity—why some gannets don't change their spots - Ewan D. Wakefield; Ian R. Cleasby; Stuart Bearhop; Thomas W. Bodey; Rachel D. Davies; Peter I. Miller; Jason Newton; Stephen C. Votier; Keith C. Hamer (Ecology, 2015)
Many established models of animal foraging assume that individuals are ecologically equivalent. However, it is increasingly recognized that populations may comprise individuals who differ consistently in their diets and foraging behaviors. For example, recent studies have shown that individual foraging site fidelity (IFSF, when individuals consistently forage in only a small part of their population's home range) occurs in some colonial breeders. Short‐term IFSF could result from animals using a win–stay, lose–shift foraging strategy. Alternatively, it may be a consequence of individual specialization. Pelagic seabirds are colonial central‐place foragers, classically assumed to use flexible foraging strategies to target widely dispersed, spatiotemporally patchy prey. However, tracking has shown that IFSF occurs in many seabirds, although it is not known whether this persists across years. To test for long‐term IFSF and to examine alternative hypotheses concerning its cause, we repeatedly tracked 55 Northern Gannets ( Morus bassanus ) from a large colony in the North Sea within and across three successive breeding seasons. Gannets foraged in neritic waters, predictably structured by tidal mixing and thermal stratification, but subject to stochastic, wind‐induced overturning. Both within and across years, coarse to mesoscale (tens of kilometers) IFSF was significant but not absolute, and foraging birds departed the colony in individually consistent directions. Carbon stable isotope ratios in gannet blood tissues were repeatable within years and nitrogen ratios were also repeatable across years, suggesting long‐term individual dietary specialization. Individuals were also consistent across years in habitat use with respect to relative sea surface temperature and in some dive metrics, yet none of these factors accounted for IFSF. Moreover, at the scale of weeks, IFSF did not decay over time and the magnitude of IFSF across years was similar to that within years, suggesting that IFSF is not primarily the result of win–stay, lose–shift foraging. Rather, we hypothesize that site familiarity, accrued early in life, causes IFSF by canalizing subsequent foraging decisions. Evidence from this and other studies suggests that IFSF may be common in colonial central‐place foragers, with far‐reaching consequences for our attempts to understand and conserve these animals in a rapidly changing environment.

Species traits and climate velocity explain geographic range shifts in an ocean‐warming hotspot - Jennifer M. Sunday; Gretta T. Pecl; Stewart Frusher; Alistair J. Hobday; Nicole Hill; Neil J. Holbrook; Graham J. Edgar; Rick Stuart‐Smith; Neville Barrett; Thomas Wernberg; Reg A. Watson; Dan A. Smale; et al. (Ecology Letters, 2015)
Species' ranges are shifting globally in response to climate warming, with substantial variability among taxa, even within regions. Relationships between range dynamics and intrinsic species traits may be particularly apparent in the ocean, where temperature more directly shapes species' distributions. Here, we test for a role of species traits and climate velocity in driving range extensions in the ocean‐warming hotspot of southeast Australia. Climate velocity explained some variation in range shifts, however, including species traits more than doubled the variation explained. Swimming ability, omnivory and latitudinal range size all had positive relationships with range extension rate, supporting hypotheses that increased dispersal capacity and ecological generalism promote extensions. We find independent support for the hypothesis that species with narrow latitudinal ranges are limited by factors other than climate. Our findings suggest that small‐ranging species are in double jeopardy, with limited ability to escape warming and greater intrinsic vulnerability to stochastic disturbances.

Emplacement of the Cabezo María lamproite volcano (Miocene, SE Spain) - Thomas M. Gernon; Samuel Spence; Clive N. Trueman; Rex N. Taylor; Eelco Rohling; Stuart J. Hatter; Ian C. Harding (Bulletin of Volcanology, 2015)

Urbanization changes the composition and bioavailability of dissolved organic matter in headwater streams - Thomas B. Parr; Christopher S. Cronan; Tsutomu Ohno; Stuart E. G. Findlay; Sean M. C. Smith; Kevin S. Simon (Limnology and Oceanography, 2015)
Population growth in cities has resulted in the rapid expansion of urbanized land. Most research and management of stream ecosystems affected by urban expansion has focused on the maintenance and restoration of biotic communities rather than their basal resources. We examined the potential for urbanization to induce bottom‐up ecosystem effects by looking at its influence on dissolved organic matter (DOM) composition and bioavailability and microbial enzyme activity. We selected 113 headwater streams across a gradient of urbanization in central and southern Maine and used elemental and optical analyses, including parallel factor analysis of excitation‐emission matrices, to characterize DOM composition. Results show that fluorescent and stoichiometric DOM composition changed significantly across the rural to urban gradient. Specifically, the proportion of humic‐like allochthonous DOM decreased while that of more bioavailable autochthonous DOM increased in the more urbanized streams. In laboratory incubations, increased autochthonous DOM was associated with a doubling in the decay rate of dissolved organic carbon as well as increased activity of C‐acquiring enzymes. These results suggest that urbanization replaces upstream humic material with more local sources of DOM that turnover more rapidly and may drive bottom‐up changes in microbial communities and affect the quality and quantity of downstream DOM delivery.

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Potential impact of invasive alien species on ecosystem services provided by a tropical forested ecosystem: a case study from Montserrat - Kelvin S.-H. Peh; Andrew Balmford; Jennifer C. Birch; Claire Brown; Stuart H. M. Butchart; James Daley; Jeffrey Dawson; Gerard Gray; Francine M. R. Hughes; Stephen Mendes; James Millett; Alison J. Stattersfield; et al. (Biological Invasions, 2015)

Determinants of maximum tree height in Eucalyptus species along a rainfall gradient in Victoria, Australia - Thomas J. Givnish; S. Chin Wong; Hilary Stuart-Williams; Meisha Holloway-Phillips; Graham D. Farquhar (Ecology, 2014)
We present a conceptual model linking dry‐mass allocational allometry, hydraulic limitation, and vertical stratification of environmental conditions to patterns in vertical tree growth and tree height. Maximum tree height should increase with relative moisture supply and both should drive variation in apparent stomatal limitation. Carbon isotope discrimination (Δ) should not vary with maximum tree height across a moisture gradient when only hydraulic limitation or allocational allometry limit height, but increase with moisture when both hydraulic limitation and allocational allometry limit maximum tree height. We quantified tree height and Δ along a gradient in annual precipitation from 300 to 1600 mm from mallee to temperate rain forest in southeastern Australia; Eucalyptus on this gradient span almost the entire range of tree heights found in angiosperms worldwide. Maximum tree height showed a strong, nearly proportional relationship to the ratio of precipitation to pan evaporation. Δ increased with ln P / E p , suggesting that both hydraulic limitation and allocational allometry set maximum tree height. Coordinated shifts in several plant traits should result in different species having an advantage in vertical growth rate at different points along a rainfall gradient, and in maximum tree height increasing with relative moisture supply, photosynthetic rate, nutrient supply, and xylem diameter.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Congenic mice reveal genetic epistasis and overlapping disease loci for autoimmune diabetes and listeriosis - Nancy Wang; Colleen M. Elso; Leanne Mackin; Stuart I. Mannering; Richard A. Strugnell; Odilia L. Wijburg; Thomas C. Brodnicki (Immunogenetics, 2014)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Multilocation Corn Stover Harvest Effects on Crop Yields and Nutrient Removal - Douglas L. Karlen; Stuart J. Birrell; Jane M. F. Johnson; Shannon L. Osborne; Thomas E. Schumacher; Gary E. Varvel; Richard B. Ferguson; Jeff M. Novak; James R. Fredrick; John M. Baker; John A. Lamb; Paul R. Adler; et al. (BioEnergy Research, 2014)

A taxonomic comparison of local habitat niches of tropical trees - Claire A. Baldeck; Steven W. Kembel; Kyle E. Harms; Joseph B. Yavitt; Robert John; Benjamin L. Turner; George B. Chuyong; David Kenfack; Duncan W. Thomas; Sumedha Madawala; Nimal Gunatilleke; Savitri Gunatilleke; et al. (Oecologia, 2013)

Use of free-standing filters in an asthma intervention study - Stuart Batterman; Liuliu Du; Edith Parker; Thomas Robins; Toby Lewis; Bhramar Mukherjee; Erminia Ramirez; Zachary Rowe; Wilma Brakefield-Caldwell (Air Quality, Atmosphere & Health, 2013)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Cue reactivity in non-daily smokers - Saul Shiffman; Michael S. Dunbar; Thomas R. Kirchner; Xiaoxue Li; Hilary A. Tindle; Stewart J. Anderson; Sarah M. Scholl; Stuart G. Ferguson (Psychopharmacology, 2013)

Long Term Performance of Hydrogeochemical Riverine Mine Tailings Deposition at Freeport Indonesia - Yuni Rusdinar; Mansour Edraki; Thomas Baumgartl; David Mulligan; Stuart Miller (Mine Water and the Environment, 2013)

Biodiversity in Hudson River shore zones: influence of shoreline type and physical structure - David L. Strayer; Stuart E. G. Findlay; Daniel Miller; Heather M. Malcom; David T. Fischer; Thomas Coote (Aquatic Sciences, 2012)

Population vulnerability to climate change linked to timing of breeding in boreal ducks - Mark C. Drever; Robert G. Clark; Chris Derksen; Stuart M. Slattery; Peter Toose; Thomas D. Nudds (Global Change Biology, 2012)
Identifying and understanding why traits make species vulnerable to changing climatic conditions remain central problems in evolutionary and applied ecology. We used spring snow cover duration as a proxy for phenological timing of wetland ecosystems, and examined how snow cover duration during spring and during the entire snow season affected population dynamics of duck species breeding in the western boreal forest of N orth A merica, 1973–2007. We predicted that population level responses would differ among duck species, such that late‐nesting species with reduced flexibility in their timing of breeding, i.e. scaup ( A ythya spp.) and scoter ( M elanitta spp.), would be more strongly affected by changing snow cover conditions relative to species better able to adjust timing of breeding to seasonal phenology, i.e. mallard ( A nas platyrhynchos ) and A merican wigeon ( A nas americana ). Population growth rates of scaup and scoter were positively linked to spring snow cover duration; after accounting for effects of density dependence, larger populations resulted after springs with long snow cover duration than after springs with short snow cover duration. In contrast, population growth rates of mallard and wigeon were either negatively or only weakly associated with snow cover duration. Duck population models were then incorporated with snow cover duration derived from climate model simulations under the A2 emission scenario, and these predictions suggested that late‐nesting duck species will experience the most severe population declines. Results are consistent with a hypothesis that the gradual climatic warming observed in the western boreal forest of N orth A merica has contributed to and may continue to exacerbate population declines of scaup and scoter.

Localised control of an introduced predator: creating problems for the future? - Thomas W. Bodey; Stuart Bearhop; Robbie A. McDonald (Biological Invasions, 2011)

Reconnecting to the Biosphere - Carl Folke; Åsa Jansson; Johan Rockström; Per Olsson; Stephen R. Carpenter; F. Stuart Chapin; Anne-Sophie Crépin; Gretchen Daily; Kjell Danell; Jonas Ebbesson; Thomas Elmqvist; Victor Galaz; et al. (Ambio, 2011)

Total mercury loadings in sediment from gold mining and conservation areas in Guyana - Joniqua Howard; Maya A. Trotz; Ken Thomas; Erlande Omisca; Hong Ting Chiu; Trina Halfhide; Fenda Akiwumi; Ryan Michael; Amy L. Stuart (Environmental Monitoring and Assessment, 2011)

Multi-parameter flow cytometry and cell sorting reveal extensive physiological heterogeneity in Bacillus cereus batch cultures - Andrew Want; Helen Hancocks; Colin R. Thomas; Stuart M. Stocks; Gerhard Nebe-von-Caron; Christopher J. Hewitt (Biotechnology Letters, 2011)

Crops that feed the world 4. Barley: a resilient crop? Strengths and weaknesses in the context of food security - Adrian Clive Newton; Andrew J. Flavell; Timothy S. George; Philip Leat; Barry Mullholland; Luke Ramsay; Cesar Revoredo-Giha; Joanne Russell; Brian J. Steffenson; J. Stuart Swanston; William T. B. Thomas; Robbie Waugh; et al. (Food Security, 2011)

Alternative (non-animal) methods for cosmetics testing: current status and future prospects—2010 - Sarah Adler; David Basketter; Stuart Creton; Olavi Pelkonen; Jan van Benthem; Valérie Zuang; Klaus Ejner Andersen; Alexandre Angers-Loustau; Aynur Aptula; Anna Bal-Price; Emilio Benfenati; Ulrike Bernauer; et al. (Archives of Toxicology, 2011)

The diet of an invasive nonnative predator, the feral ferret Mustela furo, and implications for the conservation of ground-nesting birds - Thomas W. Bodey; Stuart Bearhop; Robbie A. McDonald (European Journal of Wildlife Research, 2011)

Proposal for a revised taxonomy of the family Filoviridae: classification, names of taxa and viruses, and virus abbreviations - Jens H. Kuhn; Stephan Becker; Hideki Ebihara; Thomas W. Geisbert; Karl M. Johnson; Yoshihiro Kawaoka; W. Ian Lipkin; Ana I. Negredo; Sergey V. Netesov; Stuart T. Nichol; Gustavo Palacios; Clarence J. Peters; et al. (Archives of Virology, 2010)

An investigation into the preservation of microbial cell banks for α-amylase production during 5 l fed-batch Bacillus licheniformis fermentations - Nichola H. Hancocks; Colin R. Thomas; Stuart M. Stocks; Christopher J. Hewitt (Biotechnology Letters, 2010)

Ecological, morphological and genetic divergence of sympatric North Atlantic killer whale populations - ANDREW D. FOOTE; JASON NEWTON; STUART B. PIERTNEY; ESKE WILLERSLEV; M. THOMAS P. GILBERT (Molecular Ecology, 2009)
Ecological divergence has a central role in speciation and is therefore an important source of biodiversity. Studying the micro‐evolutionary processes of ecological diversification at its early stages provides an opportunity for investigating the causative mechanisms and ecological conditions promoting divergence. Here we use morphological traits, nitrogen stable isotope ratios and tooth wear to characterize two disparate types of North Atlantic killer whale. We find a highly specialist type, which reaches up to 8.5 m in length and a generalist type which reaches up to 6.6 m in length. There is a single fixed genetic difference in the mtDNA control region between these types, indicating integrity of groupings and a shallow divergence. Phylogenetic analysis indicates this divergence is independent of similar ecological divergences in the Pacific and Antarctic. Niche‐width in the generalist type is more strongly influenced by between‐individual variation rather than within‐individual variation in the composition of the diet. This first step to divergent specialization on different ecological resources provides a rare example of the ecological conditions at the early stages of adaptive radiation.

Papyriferic Acid, An Antifeedant Triterpene From Birch Trees, Inhibits Succinate Dehydrogenase From Liver Mitochondria - Stuart McLean; Stephen M. Richards; Siow-Leng Cover; Sue Brandon; Noel W. Davies; John P. Bryant; Thomas P. Clausen (Journal of Chemical Ecology, 2009)

Local Participation in Natural Resource Monitoring: a Characterization of Approaches - FINN DANIELSEN; NEIL D. BURGESS; ANDREW BALMFORD; PAUL F. DONALD; MIKKEL FUNDER; JULIA P. G. JONES; PHILIP ALVIOLA; DANILO S. BALETE; TOM BLOMLEY; JUSTIN BRASHARES; BRIAN CHILD; MARTIN ENGHOFF; et al. (Conservation Biology, 2009)
The monitoring of trends in the status of species or habitats is routine in developed countries, where it is funded by the state or large nongovernmental organizations and often involves large numbers of skilled amateur volunteers. Far less monitoring of natural resources takes place in developing countries, where state agencies have small budgets, there are fewer skilled professionals or amateurs, and socioeconomic conditions prevent development of a culture of volunteerism. The resulting lack of knowledge about trends in species and habitats presents a serious challenge for detecting, understanding, and reversing declines in natural resource values. International environmental agreements require signatories undertake systematic monitoring of their natural resources, but no system exists to guide the development and expansion of monitoring schemes. To help develop such a protocol, we suggest a typology of monitoring categories, defined by their degree of local participation, ranging from no local involvement with monitoring undertaken by professional researchers to an entirely local effort with monitoring undertaken by local people. We assessed the strengths and weaknesses of each monitoring category and the potential of each to be sustainable in developed or developing countries. Locally based monitoring is particularly relevant in developing countries, where it can lead to rapid decisions to solve the key threats affecting natural resources, can empower local communities to better manage their resources, and can refine sustainable‐use strategies to improve local livelihoods. Nevertheless, we recognize that the accuracy and precision of the monitoring undertaken by local communities in different situations needs further study and field protocols need to be further developed to get the best from the unrealized potential of this approach. A challenge to conservation biologists is to identify and establish the monitoring system most relevant to a particular situation and to develop methods to integrate outputs from across the spectrum of monitoring schemes to produce wider indices of natural resources that capture the strengths of each.

Spatio‐temporal variation in the strength and mode of selection acting on major histocompatibility complex diversity in water vole ( Arvicola terrestris ) metapopulations - MATTHEW K. OLIVER; XAVIER LAMBIN; THOMAS CORNULIER; STUART B. PIERTNEY (Molecular Ecology, 2009)
Patterns of spatio‐temporal genetic variation at a class II major histocompatibility complex (MHC) locus and multiple microsatellite loci were analysed within and between three water vole metapopulations in Scotland, UK. Comparisons of MHC and microsatellite spatial genetic differentiation, based on standardised tests between two demographically asynchronous zones within a metapopulation, suggested that spatial MHC variation was affected by balancing selection, directional selection and random genetic drift, but that the relative effects of these microevolutionary forces vary temporally. At the metapopulation level, between‐year differentiation for MHC loci was significantly correlated with that of microsatellites, signifying that neutral factors such as migration and drift were primarily responsible for overall temporal genetic change at the metapopulation scale. Between metapopulations, patterns of genetic differentiation implied that, at large spatial scales, MHC variation was primarily affected by directional selection and drift. Levels of MHC heterozygosity in excess of Hardy–Weinberg expectations were consistent with overdominant balancing selection operating on MHC variation within metapopulations. However, this effect was not constant among all samples, indicating temporal variation in the strength of selection relative to other factors. The results highlight the benefit of contrasting variation at MHC with neutral markers to separate the effects of stochastic and deterministic microevolutionary forces, and add to a growing body of evidence showing that the mode and relative strength of selection acting on MHC diversity varies both spatially and temporally.

From Genes to Ecosystems: The Genetic Basis of Condensed Tannins and Their Role in Nutrient Regulation in a Populus Model System - Jennifer A. Schweitzer; Michael D. Madritch; Joseph K. Bailey; Carri J. LeRoy; Dylan G. Fischer; Brian J. Rehill; Richard L. Lindroth; Ann E. Hagerman; Stuart C. Wooley; Stephen C. Hart; Thomas G. Whitham (Ecosystems, 2008)

On-line estimation of O2 production, CO2 uptake, and growth kinetics of microalgal cultures in a gas-tight photobioreactor - Niels Thomas Eriksen; Frederik Kier Riisgård; William Stuart Gunther; Jens Jørgen Lønsmann Iversen (Journal of Applied Phycology, 2007)

Dispersal of Amazonian birds in continuous and fragmented forest - Kyle S. Van Houtan; Stuart L. Pimm; John M. Halley; Richard O. Bierregaard; Thomas E. Lovejoy (Ecology Letters, 2007)
Many ecologists believe birds disappear from tropical forest fragments because they are poor dispersers. We test this idea using a spatially explicit capture data base from the Biological Dynamics of Forest Fragments Project near Manaus, Brazil. We measure bird movements directly, over relatively large scales of space and time, both before and after landscape fragmentation. We found that species which disappear from fragments move extensively between plots before isolation, but not after, and often disperse to longer distances in continuous forest than in fragmented forest. Such species also preferentially emigrate from smaller to larger fragments, showing no preference in continuous forest. In contrast, species that persist in fragments are generally less mobile, do not cross gaps as often, yet disperse further after fragmentation than before. ‘Heavy tailed’ probability models usually explain dispersal kernels better than exponential or Gaussian models, suggesting tropical forest birds may be better dispersers than assumed with some individuals moving very long distances.

Thermal range predicts bird population resilience to extreme high temperatures - Frédéric Jiguet; Romain Julliard; Chris D. Thomas; Olivier Dehorter; Stuart E. Newson; Denis Couvet (Ecology Letters, 2006)
The identification of the characteristics of species that make them susceptible or resilient to climate change has been elusive because non‐climatic influences may dominate short‐ and medium‐term changes in population and distribution sizes. Here we studied the 2003 French heat wave, during which other confounding variables remained essentially unchanged, with a correlational approach. We tested the relationship between population resilience and thermal range by analysing the responses of 71 bird species to a 6‐month heat wave. Species with small thermal ranges showed the sharpest decreases in population growth rate between 2003 and 2004 in locations with the highest temperature anomalies. Thermal range explained the resilience of birds to the heat wave independently of other potential predictors, although it correlated with nest location and broad habitat type used by species. The geographically deduced thermal range appears to be a reliable predictor of the resilience of these endothermic species to extreme temperatures.

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Importance of species interactions to community heritability: a genetic basis to trophic‐level interactions - Joseph K. Bailey; Stuart C. Wooley; Richard L. Lindroth; Thomas G. Whitham (Ecology Letters, 2006)
Recent community genetics studies have shown that specific genotypes of a host plant support distinct arthropod communities. Building upon these findings, we examined the hypothesis that a trophic community consisting of cottonwood trees, a galling herbivore and avian predators could also be related to the genetics of the host tree. We found genetic correlations among phytochemistry of individual tree genotypes, the density of a galling herbivore, and the intensity of avian predation on these herbivores. We detected significant broad‐sense heritability of these interactions that range from H = 0.70 to 0.83. The genetic basis of these interactions tended to increase across trophic levels suggesting that small genetic changes in the cottonwood phenotype could have major consequences at higher trophic levels affecting species interactions and energy flow. These findings show a heritable basis to trophic‐level interactions indicating that there is a significant genetic basis to community composition and energy flow that is predictable by plant genotype. Our data clearly link plant genetics to patterns of avian foraging and show that species interactions are important components of community heritability and ecosystem processes. Overall, these data support the hypothesis that evolution of plant traits can alter trophic‐level interactions and community composition.

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Three-dimensional Structure of an Old-growth Pseudotsuga-Tsuga Canopy and Its Implications for Radiation Balance, Microclimate, and Gas Exchange - Geoffrey G. Parker; Mark E. Harmon; Michael A. Lefsky; Jiquan Chen; Robert Van Pelt; Stuart B. Weis; Sean C. Thomas; William E. Winner; David C. Shaw; Jerry F. Frankling (Ecosystems, 2004)

Spatial and temporal assessment of sources contributing to the annual austral spring mid‐tropospheric ozone maxima over the tropical South Atlantic - ROBERT J. SWAP; THOMAS A. SZUBA; MICHAEL GARSTANG; HAROLD J. ANNEGARN; LACKSON MARUFU; STUART J. PIKETH (Global Change Biology, 2003)
The primary source of the annual austral spring mid‐tropospheric ozone maxima over the tropical South Atlantic has generally been assumed to be biomass burning. However, ozone precursor emissions from biogenic, lightning, and anthropogenic sources in subequatorial Africa before and during the ozone peak are shown to be comparable, if not greater, in magnitude to regional biomass burning production. Moreover, an investigation of the spatial and temporal characteristics of these ozone precursor sources (i.e. vegetative and microbial activity, lightning‐induced generation, and anthropogenic emissions) suggests that these alternative sources can potentially make a substantial contribution to the seasonal ozone peak. This argument is supported by the practical limitations of atmospheric transport available to regionally produced ozone and ozone precursors.

Membrane capacitance measurement using patch clamp with integrated self-balancing lock-in amplifier - Stuart L. Johnson; Martin V. Thomas; Corné J. Kros (Pflügers Archiv - European Journal of Physiology, 2002)

A randomized controlled trial of high dose ascorbic acid for reduction of blood pressure, cortisol, and subjective responses to psychological stress - Stuart Brody; Ragnar Preut; Kerstin Schommer; Thomas H. Schürmeyer (Psychopharmacology, 2002)

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

Identification, expression analysis, and mapping of B3galt6, a putative galactosyl transferase gene with similarity to Drosophila brainiac - Susan E. Cole; Meredith S. Mao; Stuart H. Johnston; Thomas F. Vogt (Mammalian Genome, 2001)

Time Lag between Deforestation and Bird Extinction in Tropical Forest Fragments - Thomas M. Brooks; Stuart L. Pimm; Joseph O. Oyugi (Conservation Biology, 1999)
Tropical forests are becoming increasingly fragmented, threatening the survival of the species that depend on them. Small, isolated forest fragments will lose some of their original species. What is uncertain is how long this process of faunal relaxation will take. We compiled data on birds in five tropical forest fragments in Kakamega Forest, Kenya, of known date of isolation. We then predicted the original and eventual species richness of these fragments and, from this difference, the eventual species losses. Expressing the losses to date as a fraction of eventual losses suggests that faunal relaxation approximates an exponential decay with a half‐life of approximately 50 years for fragments of roughly 1000 ha. In other words, in the first 50 years after isolation, tropical forest fragments of this size suffer half of the total number of extinctions that they are likely to experience. This result sets the time scale over which humanity must take conservation action in fragmented tropical forests, may aid efforts to set priorities, and indicates how high the future global extinction rate will be.

A new human prostate carcinoma cell line, 22Rv1 - R. Michael Sramkoski; Thomas G. Pretlow; Joseph M. Giaconia; Theresa P. Pretlow; Stuart Schwartz; Man-Sun Sy; Susan R. Marengo; Johng S. Rhim; Desheng Zhang; James W. Jacobberger (In Vitro Cellular & Developmental Biology - Animal, 1999)

Genomic structure, mapping, and expression analysis of the mammalian Lunatic, Manic, and Radical fringe genes - Jennifer L. Moran; Stuart H. Johnston; Cordelia Rauskolb; Jayant Bhalerao; Anne M. Bowcock; Thomas F. Vogt (Mammalian Genome, 1999)

No Evidence for Kin Discrimination in Cannibalistic Tree-Hole Mosquitoes (Diptera: Culicidae) - Thomas N. Sherratt; Sarah E. Ruff; Stuart C. Church (Journal of Insect Behavior, 1999)

Deforestation Predicts the Number of Threatened Birds in Insular Southeast Asia - Thomas M. Brooks; Stuart L. Pimm; Nigel J. Collar (Conservation Biology, 1997)
The world’s tropical forests are being cleared rapidly, and ecologists claim this is causing a massive loss of species. This claim has its critics. Can we predict extinctions from the extent of deforestation? We mapped the percentage of deforestation on the islands of the Philippines and Indonesia and counted the number of bird species found only on these islands. We then used the species‐area relationship to calculate the number of species predicted to become globally extinct following deforestation on these islands. Next, we counted the numbers of insular southeast Asian endemic bird species considered threatened—i.e., those having “a high probability of extinction in the wild in the medium‐term future”—in the latest summary Red Data Book. The numbers of extinctions predicted from deforestation and the numbers of species actually threatened are strikingly similar. This suggests we can estimate the size of the extinction crisis in once‐forested regions from the extent of deforestation. The numbers of extinctions will be large. Without rapid and effective conservation, many of the species endemic to insular southeast Asia will soon be lost.

Notes - H. C. Moore; N. J. Thomas; C. W. Metzger; E. R. Bennett; C. W. Hungerford; W M. Stuart; W M. H. Martin; E. B. Tussing; H. H. Zimmerley; H. O. Werner (American Journal of Potato Research, 1928)